Mediation Analysis of Factors Affecting the Performance of Public Schools at Early Childhood - Ehsan Bhutta، Shazia Kousar ، Chaudhary Abdul Rehman (PJE, 2023)
The main purpose of this study was to examine the factors that affect the performance of public schools for early childhood education (ECE) in Punjab, Pakistan. ECE focuses on provision of effective nutrition, health care, secure and compassionate environment and participatory opportunities for the children of 3-5 years age